The theory and practice of marketing planning for industrial goods in international markets - McDonald, Malcolm (Cranfield University, 1982)
This thesis identifies and evaluates the marketing-planning practices of British industrial goods companies operating internationally, and examines the validity of the widespread belief that formalised marketing planning facilitates success. Part I defines the theoretical framework for marketing planning and describes a logical sequence of activities leading to the setting of marketing objectives and the formulation of plans for achieving them. Part 2 contains detailed case histories describing the marketing planning practices of a sample of industrial goods companies. It also contains a summary of the results of in depth'interviews with 385 directors and senior managers from 199 companies covering a broad spectrum of size and diversity, the purpose of which was to establish the extent to which the theory is practised and what the consequences are of either conformity or non conformity. Part 3 contains conclusions and recommendations from the field- work, which revealed that 90 per cent of British industrial goods companies do not conform with the theory. This was universally true, irrespective of size and diversity. There was widespread ignorance about marketing and confusion about the difference between marketing planning and sales forecasting and budgeting, which encouraged operational managers to perpetuate an essentially parochial and short term view of business, and to extrapolate the business unchanged into the future. There was a commonality of operational problems in those companies not conforming with the theoretical framework, which centred around declining organisational effectiveness, and confusion over what to do about it. In contrast, those companies with complete marketing planning systems enjoyed high levels of organisational effectiveness, and a high degree of control over their environment. The major benefit of marketing planning derives from the process itself, rather than from the existence of a plan. This process is itself universal, irrespective of circumstances. However, what is not universal, is the degree of formalisation of the planning system, which is a function of company size-and the degree of product or market diversity. No marketing planning system will be complete unless the following conditions are satisfied: the chief executive has to understand the system and take an active part in it; there has to exist the means of integration with other functional areas'of the. business at general management level; in a closed loop system, some mechanism has to exist to prevent marketing inertia from over-bureaucratisation; operational and strategic marketing planning have to be part of the same system. Finally, the introduction of a complete marketing planning system may require a period of up to three years because it has profound organisational and phsychological ramifications, requiring, as it does, a change in the way a company manages its business.